Waywardness and Centenaries - Oviedo Pérez de Tudela, Rocío (Anales de Literatura Hispanoamericana, 2008)
Review of recente bibliography on Rubén Darío, with information on publications related to his centenary and new documents that have appeared (Arellano, D. Rhodes Whiterell, Oviedo) as well as critical tendencies, particularly in the last seven years.